Lettre de monsieur enuoyee à monseigneur pour la reformation de l'estat : ensemble la meditation de monsieur de L. ou response à la remonstrance au roy. - La Rochefoucauld, François de, 1558-1645; Albert de Luynes, Charles d', 1578-1621 ([France?] : [publisher not identified], 1620)
"La Rochefoucauld's letter to Luynes, advising him of potential dangers if he exceeds power. With a review of the downfall of the princes"--French Political Pamphlets Digital Collection, Brigham Young University.
Variant of Duvall, S.H. French Political Pamphlets Collection at the L. Tom Perry Special Collections, Harold B. Lee Library, Brigham Young University, entry 1684.
Signatures: A⁴ (last page blank).
Lindsay, R.O. French political pamphlets, 1547-1648
Also available via the World Wide Web.
Mode of access: Internet.
RBC copy: Disbound.
Keywords: La Rochefoucauld, François de, -- 1558-1645.; Albert de Luynes, Charles d', -- 1578-1621.; Albert de Luynes, Charles d', -- 1578-1621.; 1610-1643; Politics and government; France; France -- Politics and government -- 1610-1643.; France -- History -- Louis XIII, 1610-1643 -- Pamphlets; Pamphlets -- France -- Seventeenth century (dates CE).; History